(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The abstract provides a concise summary of the paper’s objectives, methods, results, and conclusions. In this case, it would explain how diversifying agricultural production can enhance resilience against climate risks. This section might include key methods, such as crop rotation, agroforestry, and integrated pest management, highlighting their potential to reduce vulnerability to climate impacts like droughts, floods, and temperature extremes.